PENINGKATAN INOVASI KERIPIK EMPING ANEKA RASA DI DESA PASIR WARU KECAMATAN MANCAK KABUPATEN SERANG - Diana Romdhoningsih; Elvin Rahmadi Ardiansyah; Mohammad Iqbal Elbetan; Ghea Auril Ifada; Mita Oktavia (Indonesian Collaboration Journal of Community Services, 2021)
The purpose of this Student Work Community Services Program is to improve the people's skills of Pasir Waru Village, Mancak District, Serang Regency. The partners of this activity are the community of melinjo chips, which are the income center in this village apart from coconut and durian. The problem faced is the lack of innovation in chips processing that attracts consumers and has a selling value. So far, it's the only one sold in the original form without any other form of processing. Implementing this service is through (1) surveys through observations, interviews, and analysis of village problems and potential, and (2) training in making chips of various flavors. The result of this program is an increase in the knowledge and skills of the community in processing or making innovations in making chips. As a result from this program is expected to improve the community's economy, especially the residents of Pasir Waru Village.